Partisipasi Masyarakat Lokal dalam Pengembangan Destinasi Wisata Berkelanjutan: Studi Kasus Situs Gunung Padang Cianjur - tatang rusata (Ministry of Tourism and Creative Economy/Tourism and Creative Economy Agency Republic of Indonesia, 2019)
Cianjur Regency has a tourist destination that attracts world tourists, namely the Gunung Padang megalithic site. As a cultural destination in the midst of the community, the development of this tourist destination faces human and environmental problems. The purpose of this study is to determine the development of tourism in Gunung Padang which involves the participation of local communities. Through a qualitative descriptive method this study analyzes the forms of community participation in developing tourism with aspects of environmental sustainability in the vicinity. The participation of the local community in the Karyamukti Village in developing the tourism site of Gunung Padang is done by forming a community of lovers of Gunung Padang which is an embryo for the formation of the Tourism Driving Group or Kompepar. It can be concluded that there are positive benefits felt by the local community in the form of opening opportunities to open businesses that can improve the economic level of encouraging people to be more active in doing business and developing tourism in the region. However, the benefits of high mining are still a pressure on environmental sustainability in the region.